Systematic review of economic evaluations of interventions for high risk young people - Kim Edmunds; Rod Ling; Anthony Shakeshaft; Chris Doran; Andrew Searles (BMC, 2018)
Abstract Background The aim of this systematic literature review is to identify and critique full economic evaluations of interventions for high risk young people with the purpose of informing the design of future rigorous economic evaluations of such intervention programs. Methods A PRISMA compliant search of the literature between 2000 and April 2018 was conducted to identify full economic evaluations of youth focussed interventions for at risk young people. Duplicates were removed and two researchers independently screened the article titles and abstracts according to PICOS criteria for exclusion and inclusion. The remaining full text articles were assessed for eligibility and a quality assessment of the included articles was conducted using the Drummond checklist. Results The database, grey literature and hand searches located 488 studies of interventions for at risk young people. After preliminary screening of titles and abstracts, 104 studies remained for full text examination and 29 empirical studies containing 32 separate economic evaluations were judged eligible for inclusion in the review. These comprised 13 cost-benefit analyses (41%), 17 cost-effectiveness analyses (53%), one cost-utility analysis (3%) and a social return on investment (3%). Three main methodological challenges were identified: 1. attribution of effects; 2. measuring and valuing outcomes; and 3. identifying relevant costs and consequences. Conclusions A cost-benefit analysis would best capture the dynamic nature of a multi-component intervention for high risk young people, incorporating broader intersectoral outcomes and enabling measurement of more domains of risk. Prospective long-term data collection and a strong study design that incorporates a control group contribute to the quality of economic evaluation. Extrapolation of impact into the future is important for this population, in order to account for the time lag in effect of many impacts and benefits arising from youth interventions.